In vivo assessment of the Optipen optical reflectometer for detecting enamel surface changes following an erosive challenge - Ana Luiza Bogaz Debortolli; Franciny Querobim Ionta; Ana Laura Marques Xavier; Carolina Ruis Ferrari; Thiago Saads Carvalho; Adrian Lussi; Marília Afonso Rabello Buzalaf; Daniela Rios (Clinical Oral Investigations, 2026)
Abstract Objectives To evaluate whether the Optipen optical reflectometer can detect enamel surface changes associated with erosion under clinical conditions. Materials and methods In this short-term parallel randomized clinical trial, 24 healthy participants were allocated to two groups: Test (T-rinse with a cola beverage for 30 s) and Control (C-rinse with water). Surface reflectance was measured using the Optipen optical reflectometer on the maxillary central incisors at baseline, immediately after rinsing, and after 2 h of salivary exposure, and expressed as the percentage of surface reflection intensity. Results The test group showed significantly lower reflectance values immediately after the erosive challenge (65.4) compared with the control group (102) ( p < 0.05). After 2 h of salivary exposure, no significant differences were observed between groups (T = 85.7 and C = 97.8). Conclusions The Optipen optical reflectometer detected immediate changes in enamel surface reflectance in vivo following a single erosive challenge. Clinical relevance This device may be useful for detecting immediate enamel surface changes following erosion. Further studies are needed to optimize reflectance measurements after salivary exposure.